Effect of dietary tannins on the performance, lymphoid organ weight, and amino acid ileal digestibility of broiler chickens: A meta-analysis - Hidayat, Cecep (Vet World, 2021)
BACKGROUND AND AIM: Tannins are functional secondary metabolites that may provide benefits to ruminants. However, to date, their effects on broiler chickens remain inconclusive. This study aimed to evaluate the effectiveness of dietary tannin levels on the performance, body organs, and amino acid (AA) digestibility of broiler chickens using a meta-analysis. MATERIALS AND METHODS: After verification and evaluation, a total of 22 articles were included in the present study. All data regarding dietary tannin dosages, performance, digestibility, and gastrointestinal physiology of broiler chickens were tabulated into a database. The database data were then statistically analyzed using mixed models, with tannin dose as a fixed effect and study as a random effect. RESULTS: High levels of dietary tannins negatively affected the average daily gain and average daily feed intake of broiler chickens according to linear patterns (p<0.001). In addition, dietary tannins decreased drumstick and liver weights, as well as bursa of Fabricius and spleen weight (p<0.05). Meanwhile, other carcass traits (i.e., thigh, wings, and body fat) were not influenced by dietary tannins. Regarding AA digestibility, high dietary tannin concentrations induced negative responses on isoleucine, leucine, and methionine digestibility (p<0.05). CONCLUSION: Dietary tannins appear to have a negative effect on broiler performance, lymphoid organ weight, and AA ileal digestibility. Hence, the addition of tannins to broiler diets is not recommended.